Identification and characterisation of gut microflora of frugivorous bats from Sarawak - Fatiyah, Md Kilau (Universiti Malaysia Sarawak (UNIMAS), 2015)
Information that is carried by microbiota community is complex and valuable. However, this information is very limited and only few studies have reported on this. Gastrointestinal tract of bats composed of complex community of microbes and they are well-known as a natural reservoir of zoonotic diseases. Thus, this study aims to discover the microbe diversity in the gut of frugivorous bats from various localities in Sarawak.